Stochastic Modeling and Simulation of Photopolymerization Process - ÇİFTÇİOĞLU, GÖKÇEN ALEV (WILEY-BLACKWELL, 2011)
In this study, the effect of photoinitiator concentration on the gelation time of different resins were studied in the absence of oxygen in the reaction volume by using passive microrheology technique. Four different monomers which are ethoxylated pentaerythritol tetraacrylate (SR494), trimethylolpropane triacrylate (SR351), Methylene glycol diacrylate (SR272), and 2(2-ethoxyetoxy) ethyl acrylate (SR256) were used in these experiments. Resins were prepared from these four different monomers by mixing them with various amount of 2,2-dimethoxy 1,2-diphenylethanone photoinitiator molecule with high absorption coefficient at the frequency of UV light used in these experiment. The simulations of the results obtained from microrheology experiments were carried out with the new model based on the stochastic Monte Carlo approach in order to account for the inherently random and discrete nature of the photopolymerization reactions. The model captures the nonlinear decrease of gelation time with increasing photoinitator concentration and number of acrylate fragments on each monomer. POLYM. ENG. SCI., 51:1710-1719, 2011. (C) 2011 Society of Plastics Engineers
Keywords: PARTICLE-TRACKING MICRORHEOLOGY; DIFFUSING WAVE SPECTROSCOPY; FREE-RADICAL POLYMERIZATION; COUPLED CHEMICAL-REACTIONS; COMPLEX FLUIDS; TERMINATION; LENGTH; COPOLYMERIZATION; PARAMETERS; KINETICS